Cutting Edge Curve Design Method of Large Module Hobbing Cutter Based on Profile Modifications - Qu Tie; Xin Wen; Yang Jianjun; Han Chunyang; Wei Bingyang (Jixie chuandong)
In the process of large module gear hobbing of high-order modification tooth profile, the cutting edge curve is different according to the variation of rake angle, which has a great influence on tooth profile accuracy. Thus the 2-degree envelope method is applied to the gear hobbing process to obtain the hobbing contact trace between the tooth surface and the base worm of the hobbing cutter. The cutting edge curve is calculated based on the different rake angles of the hobbing cutter. The shape and the slope of the cutting edge are analyzed, which provides the reference for the design and measurement of hobbing cutter edge. In the end, a modified gear profile is hobbed and measured to verify the above design method.